2014
DOI: 10.1590/0102-311x00168412
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequalities and exposure to traffic-related air pollution in the city of São Paulo, Brazil

Abstract: Air pollution is a leading public health concern. In addition, poor populations have been reported as showing increased exposure to such pollution. The current study thus aimed to evaluate the socioeconomic status of the population exposed to vehicle-related air pollution in the city of São Paulo, Brazil. The study used data from the 2010 Census on head-of-household’s mean monthly income and the percentage of households connected to the sewage system. Exposure to air pollutants was estimated according to traff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 12 publications
(19 reference statements)
1
9
0
4
Order By: Relevance
“…Ferreira et al 30 avaliaram em São José dos Campos (São Paulo) os efeitos do material particulado e seus constituintes químicos na internação hospitalar de indivíduos ≥ 60 anos, concluindo que o risco de hospitalização por doenças respiratórias aumentou 23,5% (IC95%: 13,5-34,3) e 12,8% (IC95%: 6,0-20,0) para cada 10µg/m 3 se os níveis para este poluente se mantiverem os mesmos referentes ao ano de 2011, haverá cerca de 953 mil internações hospitalares públicas e um gasto público estimado de mais de R$ 1,6 bilhão 31 . Habermann et al 32 avaliaram a situação socioeconômica da população do Município de São Paulo exposta aos poluentes do tráfego, sendo a exposição aos poluentes estimada pela densidade de fluxo veicular por setor censitário com uma faixa adicional de 200 metros, concluindo que quanto maior o nível socioeconômico maior a exposição. Entendemos que quando se analisa como desfecho a internação por câncer do aparelho respiratório tem de se levar em conta a facilidade de acesso aos centros de saúde.…”
Section: Discussionunclassified
“…Ferreira et al 30 avaliaram em São José dos Campos (São Paulo) os efeitos do material particulado e seus constituintes químicos na internação hospitalar de indivíduos ≥ 60 anos, concluindo que o risco de hospitalização por doenças respiratórias aumentou 23,5% (IC95%: 13,5-34,3) e 12,8% (IC95%: 6,0-20,0) para cada 10µg/m 3 se os níveis para este poluente se mantiverem os mesmos referentes ao ano de 2011, haverá cerca de 953 mil internações hospitalares públicas e um gasto público estimado de mais de R$ 1,6 bilhão 31 . Habermann et al 32 avaliaram a situação socioeconômica da população do Município de São Paulo exposta aos poluentes do tráfego, sendo a exposição aos poluentes estimada pela densidade de fluxo veicular por setor censitário com uma faixa adicional de 200 metros, concluindo que quanto maior o nível socioeconômico maior a exposição. Entendemos que quando se analisa como desfecho a internação por câncer do aparelho respiratório tem de se levar em conta a facilidade de acesso aos centros de saúde.…”
Section: Discussionunclassified
“…We used socioeconomic data from the last Brazilian census available (2010) in order to assess potential population exposure to the high ozone concentrations during the extreme episode. Previous exposure studies with different types of modelling in São Paulo used grid cells of 750 m [15] or 2 km [13], therefore, we used the weighting areas from the census, which are larger aggregations of the census tracts by population, for a better match with the WRF/Chem spatial resolution grid of 1 km 2 . The maps with the areas of exceedance of each limit were joined with the MASP weighting areas in order to obtain the estimated number of residents inside the area of exceedance of each limit.…”
Section: Socioeconomic and Health Vulnerabilitymentioning
confidence: 99%
“…The spatial variation of life expectancy in the municipality of São Paulo alone ranges from 58 to 81 years of age [8]. Several studies worldwide investigated air pollution exposure according to socioeconomic conditions, showing that the lower-income population, elderly and children are more vulnerable to the effects of air pollution [9][10][11][12], similarly to São Paulo [13][14][15]. Recent studies on vulnerability to high temperature and air pollution demonstrated how the intraurban spatial variation of environmental conditions are associated to exposure and health effects, but additional studies are needed for a better assessment of these relationships [16].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that poor people, from underprivileged minorities, are the ones who mostly end up living in the most industrialized and polluted places 11,12,13,14,15 . For instance, a recent study conducted in England 16 showed an unequal distribution of industrial sites, with these installations disproportionately located in deprived areas and near deprived populations.…”
Section: Introductionmentioning
confidence: 99%